Heritabilitas dan Hubungan Antar Karakter Kuantitatif Kecipir (Psophocarpus tetragonolobus (L.) DC) pada Tiga Lingkungan - Dian Rakhmad; Muhamad Syukur; Willy Bayuardi Suwarno (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2021)
Winged bean (Psophocarpus tetragonolobus (L.) DC) is known as tropical soybean with high nutritional content. Lack of information on the variance components and heritability of winged bean breeding is one of the reasons for the lack of winged bean breeding programs in Indonesia. This reseach aimed to obtain information on variance components, heritability and relationship between winged bean traits. The experiment was conducted in three environments, from January 2019 to June 2020. Two environments located in Bogor and one in Palembang. Eleven genotypes of winged bean were tested and 11 traits were observed. The result showed that flowering time and seed number per pod performed wide genetic variability. High heritability was observed on seed number per pod (89.48%), flowering time (83.32%), young pods length (70.97%), and weight of 100 seeds (68.63%). The results of correlation analysis and path analysis showed that young pod productivity (1.07), seed weight per plot (0.81), flowering time (0.29), young pod length (0.17), young pod width (0.12), seed weight per plant (0.09), and 100 seeds weight (0.01) had a positive direct effect on wing bean productivity. Flowering time, seed number per pod, seed weight per plant are suitable characters for selection criteria for breeding high productivity winged bean. Keywords: correlation, genetic variability, path analysis